Blockade of Piezo2 Pathway Attenuates Inflammatory and Neuropathic Pain in the Orofacial Area - Min-Jeong Jo; Jo-Young Son; Yu-Mi Kim; Jin-Sook Ju; Min-Kyoung Park; Min-Kyung Lee; Dong-Kuk Ahn (Pain Research and Management)
Although previous studies suggest that Piezo2 regulates chronic pain in the orofacial area, few studies have reported the direct evidence of Piezo2’s involvement in inflammatory and neuropathic pain in the orofacial region. In this study, we used male Sprague Dawley rats to investigate the role of the Piezo2 pathway in the development of inflammatory and neuropathic pain. The present study used interleukin (IL)-1β–induced pronociception as an inflammatory pain model. Subcutaneous injection of IL-1β produced significant mechanical allodynia and thermal hyperalgesia. Subcutaneous injection of a Piezo2 inhibitor significantly blocked mechanical allodynia and thermal hyperalgesia induced by subcutaneously injected IL-1β. Furthermore, the present study also used a neuropathic pain model caused by the misplacement of a dental implant, leading to notable mechanical allodynia as a consequence of inferior alveolar nerve injury. Western blot analysis revealed increased levels of Piezo2 in the trigeminal ganglion and the trigeminal subnucleus caudalis after inferior alveolar nerve injury. Furthermore, subcutaneous and intracisternal injections of a Piezo2 inhibitor blocked neuropathic mechanical allodynia. These results suggest that the Piezo2 pathway plays a critical role in the development of inflammatory and neuropathic pain in the orofacial area. Therefore, blocking the Piezo2 pathway could be the foundation for developing new therapeutic strategies to treat orofacial pain conditions.